Case Report: Giant abdominal hemangioma originating from the liver - Jiang, Tianxiang; Zhao, Zhou; Cai, Zhaolun; Shen, Chaoyong; Zhang, Bo (Frontiers in Oncology, 2023)
Background Hepatic hemangioma is among the most common benign liver lesions. However, giant pedunculated hepatic hemangiomas are exceptionally rare and associated with additional risks, such as torsion.We present the case of a 63-year-old female patient who presented with abdominal distension and pain. Barium meal examination and gastroscopy revealed a large, smoothsurfaced submucosal bulge located at the fundus of the stomach. Subsequent MRI examination identified a mass measuring approximately 6.4 x 7 cm in the left upper abdomen. Surgical intervention was planned for mass removal. However, intraoperative exploration revealed the origin of the mass to be the liver, and subsequent histopathological examination confirmed it as a hemangioma.We systematically summarized the characteristics of our case along with 31 previously reported cases. Giant pedunculated hepatic hemangiomas typically occur in the left lobe of the liver. Due to their atypical presentation, a combination of imaging methods such as ultrasound, CT, and/or MRI is essential for accurate diagnosis. Furthermore, surgical intervention is recommended due to the potential risks of bleeding, rupture, and torsion.